Characterization and selection of Citrus sinensis Osbeck cv. Margaritera parental trees for repopulation in the Mompox depression region, Colombia - Yacomelo Hernández, Marlon José; Baquero, Cesar; Martínez, Mauricio; Murcia, Nubia; Correa, Ender; Orduz Rodriguez, Javier Orlando (Universidad Nacional de Colombia, 2025)
At the Mompox depression region, located in the lower valley of the Magdalena River, citrus trees and especially the orange cultivar Margaritera (Citrus sinensis Osbeck) are cultivated by small producers. The effects of the rainy season during 2010 and 2011 caused the loss of ca. 80% of the planted area in some municipalities. The main objective of this study was to select outstanding genotypes according to fruit quality attributes based on the Colombian Technical Standard NTC4086. This selection was carried out by collecting and characterizing 120 Margaritera orange genotypes represented by three clones: Margarita, Azúcar and Criollo. The characterization was performed using 14 fruit descriptors regulated by the parameters of the International Plant Genetic Resources Institute. Outstanding clones were chosen using a selection index based on attributes such as juice percentage and maturity index. The fruit characterization showed variability for all the descriptors evaluated, especially those related to size, weight and acidity (explained 51.76% of the total variability). Furthermore, these contributed mostly to comprise three phenotypic groups conformed by 79, 23 and 18 genotypes, respectively. Eight outstanding genotypes were selected for quality attributes: four Margarita clones, two Azúcar clones and two Criollo clones; these became a source of guaranteed propagation material in the region.